A linear programming approach to optimize natural rubber production / Sarimah Baharudin and Noraini Noordin - Baharudin, Sarimah; Noordin, Noraini (UiTM Cawangan Perlis, 2017)
This article describes the design of a linear programming model to optimize production of natural rubber in Malaysia. Uptrend in natural rubber production which occurred after 2015 did not last long. Area for rubber cultivation was not only affected by efforts to convert rubber estates into real estate developments but also by factors such as increase in farmers' interest to cultivate oil palm, unstable rubber price, lengthy duration of low rubber price, insufficient number of rubber tappers, long waiting time before tapping rubber trees, changing land conditions for crops, and buyout offers for rubber wood from furniture - manufacturing factories. Results from two different software, namely Excel Solver and QM for Windows were compared. No significant difference in value was observed to take place , thus the development of linear programming model was considered to be successful.